Benzoxadiazole and Benzoselenadiazole as π‐Bridges in Nonfullerene Acceptors for Efficient Polymer Solar Cells. Issue 11 (22nd August 2018) - Nian, Yaowen; Pan, Feilong; Li, Suhan; Jiang, Haiying; Feng, Shizhen; Zhang, Lianjie; Cao, Yong; Chen, Junwu
Abstract: Fused‐ring electron acceptors with acceptor‐donor‐acceptor (A‐D‐A) structure have become a hot research field in recent years. In this work, 2, 1, 3‐benzoxadiazole (BO) and 2, 1, 3‐benzoselenadiazole (BS) were introduced as π‐bridges between indaceno [1, 2‐ b  : 5, 6‐ b ′] dithiophene (IDT) cores and rhodanine termini for two nonfullerene acceptors IDTBOR and IDTBSR, to compare the structure‐property relationship. Inserting BO as the π‐bridge afforded IDTBOR with deeper LUMO and HOMO levels, whereas BS‐based IDTBSR possessed a smaller optical band gap. With PBDB‐T as polymer donor, IDTBOR‐ and IDTBSR‐based solar cells showed power conversion efficiencies of 7.74 and 6.95%, respectively. A higher open‐circuit voltage of 0.95 V was found for IDTBSR, owing to its up‐lying LUMO level. A higher short‐circuit current density of 15.98 mA/cm 2 and fill factor of 54.67% were achieved for IDTBOR, mainly because of the higher electron mobility and better structure order in the blend film. The results suggest that BO and BS units are valuable π‐bridges to construct efficient nonfullerene acceptors. Abstract : It's BOB'S :2, 1, 3‐Benzoxadiazole (BO) and 2, 1, 3‐benzoselenadiazole (BS) were introduced as π‐bridges between an indaceno [1, 2‐ b  : 5, 6‐ b ′] dithiophene (IDT) core and a rhodanine terminus for two nonfullerene acceptors IDTBOR and IDTBSR, to compare their structure‐property relationship. With PBDB‐T as polymer donor, IDTBOR‐ and IDTBSR‐based solar cells showed power conversion efficiencies of 7.74 and 6.95%, respectively.